Pervaporation via silicon‐based membranes: Correlation and prediction of performance in pervaporation and gas permeation. Issue 7 (17th February 2021) - Moriyama, Norihiro; Kawano, Yuta; Wang, Qing; Inoue, Ryota; Guo, Meng; Yokoji, Makoto; Nagasawa, Hiroki; Kanezashi, Masakoto; Tsuru, Toshinori
Abstract: Pervaporation (PV) is a membrane technology that holds great promise for industrial applications. To better understand the PV mechanism, PV dehydrations of various types of organic solvents (methanol, ethanol, iso‐propanol, tert‐butanol, and acetone) were performed on five types of organosilica and two types of silicon carbide‐based membranes, all with different pore sizes. Water permeance was dependent on the types of organic aqueous solutions, which suggested that organic solvents penetrated the pores and hindered the permeation of water. In addition, water permeance of various types of membranes in PV was well correlated with hydrogen permeance in single‐gas permeation. Furthermore, a clear correlation was obtained between the permeance ratio in PV and that in single‐gas permeation, which was confirmed via the modified‐gas translation model. These correlations make it possible to use single‐gas permeation properties to predict PV performance.